Synesthetic Colors for Japanese Scripts in Japanese Synesthetes - Kazuhiko Yokosawa (i-Perception, 2011)
The determinants of synesthetic colors for Japanese scripts were studied in six Japanese grapheme-color synesthetes. We investigated the influence of linguistic properties such as phonology, orthography, and meaning on synesthetic colors for logographic characters (Kanji), phonetic characters (hiragana and katakana), and digits. From a palette of 138 colors, the synesthetes selected colors for 79 Kanji, 71 hiragana, and 71 katakana characters, and 9 digits. The results revealed that the color choices for hiragana and katakana characters representing the same sound were remarkably consistent, indicating that color selection depended on phonology and not visual form. On the other hand, synesthetic colors for Kanji characters, which are usually learned later, depended on meaning and phonology. Kanji characters representing concepts that are highly related to colors (eg, names of objects with typical colors) were associated with those colors. Digits and corresponding Kanji numerals elicited strikingly similar colors. Colors for Kanji and hiragana characters sharing the same sound were likely to be similar. These results suggest that synesthetic colors are generalized from digits and phonetic scripts to Kanji characters via meaning and phonology. This study provides insights into the generalization of synesthetic colors to later acquired sets of graphemes within a language.